'A man after god's own heart': charisma, masculinity and leadership at a charismatic Church in Brighton and Hove, UK. Issue 3 (2nd July 2016) - Wignall, Ross
Abstract : This article suggests that the gendered aspects of charisma have so far been overlooked in recent scholarship and seeks to align studies of charismatic religious leaders more fully with studies of masculinity and the 'masculinisation' of Charismatic churches. Based on research conducted at the Church of Christ the King (CCK) in Brighton and Hove, UK, I analyses how leadership operates as a key language for mediating masculinity, giving young men ways of being manly within both Christian and church parameters as well as forming links between experienced leaders and their young apprentices. Focusing on a dramatic visit by a notorious international preacher as an instance of charismatic masculinity in action, the author shows how an understanding of a corporate culture of masculinity can lend new insight into our understanding of charisma as both a relational construct and a system of individual authority which is tested at times of crisis and succession.